PELATIHAN PEMBUATAN SABUN CAIR KEPADA ANGGOTA PKK DESA TANJUNG BENUANG - Arista Ratih; Eni Yulianti; Pitri Handayani; Eko Wulandari; Leni Marlina; Rozana Zuhri; Juanita Hibatullah; Widia Putri Febriani; Wisnu Pamungkas; Andri Darmawangsah (AbdiMasya | Hira Institute, 2025)
The training on making liquid soap from used cooking oil was carried out as a solution to the problem of household waste and MSMEs in Tanjung Benuang Village, Merangin Regency. This activity aims to increase the knowledge, skills, and environmental awareness of PKK members in processing used oil waste into valuable products. The methods used include counseling, demonstrations, hands-on practice, and evaluation through participant satisfaction questionnaires. The results showed an increase in participants' understanding of the dangers of used cooking oil and liquid soap-making skills, as well as the emergence of motivation to produce soap independently and even for sale. Evaluations show a program success rate of 99%. This activity not only provides soft skills but also encourages PKK cadres to become agents of change in sustainable household waste management